A theoretical study of the electronic properties of hydrogenated spherical-like SiC quantum dots with C-rich and Si-rich compositions - Ojeda-Martínez, Miguel (2024)
Quantum dots have many potential applications in opto-electronics, energy storage, catalysis, and medical diagnostics, silicon carbide quantum dots could be very attractive for many biological and technological applications due to their chemical inertness and biocompatibility, however, there are seldom theoretical studies that could boost the development of these applications. In this work, the electronic properties of hydrogenated spherical-like SiC quantum dots with C-rich and Si-rich compositions are investigated using density functional theory calculations. The quantum dots are modeled by removing atoms outside a sphere from an otherwise perfect SiC crystal, the surface dangling bonds are passivated with H atoms. Our results exhibit that the electronic properties of the SiC-QD are strongly influenced by their composition and diameter size. The energy gap is always higher than that of the crystalline SiC, making these SiC QD's suitable for applications at harsh temperatures. The density of states and the energy levels show that the Si-rich quantum dots had a higher density of states near the conduction band minimum, which indicates better conductivity. These results could be used to tune the electronicproperties of SiC quantum dots for optoelectronic applications.